Collagen crosslinking in thin corneas - Aniruddh Heroor; Rashmi Deshmukh (Indian Journal of Ophthalmology)
Background: Collagen cross linking (CXL) is the only modality that can arrest or mitigate the progression of keratoconus. However, conventional CXL using the Dresden protocol cannot be used in corneas less than 400 µm in thickness due to the risk of endothelial damage. A number of modifications have been implemented to solve this problem. Purpose: To highlight the parameters used in the Dresden protocol, its pitfalls in thin corneas and elucidate the modifications that allow cross-linking in thin corneas. Synopsis: This video serves to present the Dresden protocol, the ensuing problem in thinner corneas and elucidate the myriad of interesting alternatives currently available to tackle this difficulty. Video Link: https://youtu.be/-7CRZQ7NGXA